The heterogeneous reaction of ozone with soot aerosol - Kamm, Stefan; Möhler, Ottmar; Naumann, Karl-Heinz; Saathoff, Harald; Schurath, Ulrich (Atmospheric environment, 1999)
The loss of ozone on carbon soot aerosol was investigated in the temperature range 238-330K for reaction times up to 72h: 200μg m−3 ozone in dry synthetic air is depleted with an initial reaction probability γ=1.2×10−6 at 296K. The reaction probability decreases with a characteristic time τ of about 12h (1/τ=k3=(2.3±0.6)×10−5s−1) due to surface passivation. The reaction rate has a positive temperature dependence, and a complex negative dependence on the ozone concentration. A minimum set of four quasi-elementary reactions is required to model the observed concentration and time dependencies of the ozone loss rate: rapid destruction of one monolayer equivalent of ozone on pristine surface sites (SS): SS+O3→SSO+O2 (I), ozone-induced recovery of reactive sites: SSO+O3→SS+2O2 (or SS'+O2+CO2) (IIa,b), spontaneous recovery of reactive sites: SSO→SS'+CO, and spontaneous site passivation: SSO→SSp (III). The kinetic parameters γ2ab,k2c, and k3, which were determined in 11 independent experiments, lead to the following analytical expression for the effective reaction probability γeff which applies when the fast initial surface oxidation has reached a steady state:γeff=[2γ2ab+2.6×1015k2c/([O3]〈c〉)]exp(−k3t).This equation is valid over a wide range of atmospheric conditions. It implies that ozone depletion on dry soot aerosol is negligible both in the troposphere and lower stratosphere.
Gesehen am 08.10.2020